MEDIASI DALAM PENYELESAIAN SENGKETA PROSES PEMILU: TINJAUAN PSIKOLOGI (Jurnal Huma Betang Demokrasi, 2021)
In a country that adheres to a democratic system, General Elections are an important instrument. Indonesia is a democratic country that has held Simultaneous Elections in 2019. Conceptual elections are a means of implementing people's sovereignty. The 2019 elections are held based on Law Number 7 of 2017 concerning General Elections. In the implementation of elections, it is very possible for disputes to occur at several stages. One of them is process dispute. In the Election Law, one of the tasks and authorities given to Bawaslu is the resolution of electoral process disputes. Article 466 of the Election Law states that: Election Process Disputes include disputes that occur between Election Contestants and disputes between Election Contestants and Election Organizers as a result of the issuance of KPU Decrees, Province KPU Decrees and Regency KPU Decrees. The dispute resolution of the election process begins with mediation. Mediation can provide a solution for the disputing parties. Mediation is a method of resolving disputes through a negotiation process to obtain an agreement between the parties with the assistance of a mediator. Psychology is one of the crucial dimensions in the application of mediation. The mediator needs to have basic knowledge of psychology. Psychological aspects cannot be ignored in the mediation of dispute resolution in the election process.